Factors influencing the dative/genitive variation in Croatian - Stanojević, Mateusz-Milan (2010)
The Croatian dative has a variety of uses: allative (self-propelled motion: vratiti se kući-DAT 'to return home-DAT'), competitor (competing energies: protiviti se proglašenju-DAT 'oppose the declaration-DAT'), transfer (transfer or elements towards the dative: Daj mi-DAT sablju-ACC 'Give me-DAT a sword-ACC'), assessment (assessing the status of an entity within the dative's dominion: knjiga-NOM joj-DAT je bila zabavna 'she-DAT found the book amusing' lit. the book was amusing to her) and several other minor uses (cf. Stanojević and Geld 2008). Usually, the dative is governed by a verb (such as vratiti se, protiviti se, dati) and constructions such as biti kakav kome (the so-called free dative). In the allative and competitor examples the dative may be governed by prepositions such as prema ‘towards’, k ‘to’, nadomak ‘close to’, nadohvat 'close to', nasuprot 'as opposed to', usuprot 'as opposed to', naprama 'in relation to' unatoč ‘despite’, uprkos/usprkos ‘despite’. While prema and k appear only with the dative case, the remaining eight prepositions may appear with the dative and the genitive case, as illustrated in the following examples with nasuprot: (1) palač[a] koja se nalazi nasuprot crkvi sv. Mateja… palace which refl. situate across from church-DAT Saint Matthew… ‘… the palace which is across from St. Matthew’s church…’ (2) …žuta zgrada … koja se smjestila nasuprot župne …yellow building … which refl. locate across from parish-GEN crkve sv. Ćirila i Metoda church-GEN Saint Cyril and Methodius ‘…the yellow building … across from the parish church of Saints Cyril and Methodius’ Both (1) and (2) describe the position of a building relative to a church, but the reference point in (1) is in the dative case (crkvi ‘church’-DAT), whereas in (2) it is in the genitive case (crkve ‘church-GEN). A similar pattern of variation also appears with the other seven prepositions. The aim of this paper is to explore the dative-genitive variation between the following prepositions: nasuprot ‘across from, as opposed to’, nadomak ‘close to’, nadohvat ‘within reach’, usuprot ‘in opposition to’, unatoč ‘despite’, usprkos/uprkos ‘despite’ and naprama ‘to’, based on the data from the Croatian National Corpus. We will try to prove that the variation between the dative and the genitive is the result of the interplay between semantic, ecological, and structural factors. Semantically, the variation is possible because the allative and competitor meanings expressed by these prepositions, being diachronically oldest, do not require mental contact between the dative and the trajector (i.e. the dative may be a non-affected reference point), which coincides with the reference-point meaning of the genitive. Ecologically, some types of referents may favor the dative or the genitive: persons are more likely to be used in the dative because of the current dative prototype (the prototypical transfer sense requires a potentially affected dative) ; numbers appear with non-dative structures, possibly because of a complex dative paradigm. Structurally, occasional postpositions (oborinama-DAT usprkos 'despite the rain') require the dative (whereas prepositions may take the dative and the genitive), probably because they "tap into" a diachronically older structure. We will investigate the strength and constraints of each factor, their hierarchy and their possible implications for dative acquisition and its description for native and non-native speakers.